Analysis of Factors Influencing Domestic Tourists Decisions to Visit International Destinations: A Case Study of the North Sumatra Region - Br Karo, Aulia Maharani Putri; Dewi Yanti; Muhammad Khadry (International Journal of Travel, Hospitality and Events, 2025)
This study aims to analyze the factors that influence the decision to visit domestic tourists from North Sumatra to foreign destinations. The research method uses a quantitative explanatory approach with data collection techniques through questionnaires to 100 respondents selected purposively. Data analysis was carried out using multiple linear regression using SPSS. The results showed that of the seven independent variables studied, only tourism promotion (X4) and hobbies and interests (X8) had a significant effect on the decision to visit (Y), with coefficients of 0.175 and 0.376, respectively. Meanwhile, personal motivation (X2), tourism products (X3), income (X5), recommendations (X6), and the environment (X7) did not show a significant effect. The R² value of 0.704 indicates that 70.4% of the variation in the decision to visit can be explained by the variables in the model. These findings focus on the importance of effective promotion strategies and adjusting domestic tourist destinations to the interests of the younger generation to increase the competitiveness of local tourism. Research recommendations include strengthening digital promotion, developing interest-based tour packages, and improving destination facilities and accessibility. Keywords: Analysis Factor, Domestic Tourists, Visiting Decisions, North Sumatra.